2018
DOI: 10.1144/sp470.2
|View full text |Cite
|
Sign up to set email alerts
|

The Jan Mayen microplate complex and the Wilson cycle

Abstract: The opening of the North Atlantic region was one of the most important geodynamic events that shaped the present-day passive margins of Europe, Greenland and North America. Although well-studied, much remains to be understood about the evolution of the North Atlantic, including the role of the Jan Mayen Microplate Complex (JMMC). Geophysical data provide an image of the crustal structure of this microplate and enable a detailed reconstruction of the rifting and spreading history. However, the mechanisms that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 184 publications
(290 reference statements)
0
37
0
Order By: Relevance
“…Prior to breakup, the proto-North Atlantic was an amalgamation of Archean and Proterozoic terranes (Kerr et al, 1996;St-Onge et al, 2009), with the structures in these preexisting terranes known to have exerted considerable influence on rift evolution (Doré et al, 1997;Ady and Whittaker, 2018;Peace et al, 2018aPeace et al, , 2018bSchiffer et al, 2018a;Heron et al, 2019).…”
Section: Opening Of the North Atlanticmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to breakup, the proto-North Atlantic was an amalgamation of Archean and Proterozoic terranes (Kerr et al, 1996;St-Onge et al, 2009), with the structures in these preexisting terranes known to have exerted considerable influence on rift evolution (Doré et al, 1997;Ady and Whittaker, 2018;Peace et al, 2018aPeace et al, , 2018bSchiffer et al, 2018a;Heron et al, 2019).…”
Section: Opening Of the North Atlanticmentioning
confidence: 99%
“…This question of scale essentially refers to a block that is surrounded by rifts (or spreading centres) rather than a single graben. Although the aforementioned different types of continental fragments have distinct origins and structures, the preservation, and sometimes isolation of such entities is considered to be often highly controlled by structural inheritance (Schiffer et al, 2018b). Moreover, continental fragments have the potential to introduce complexities into conjugate margin studies for reasons that become apparent when considering the structural evolution of the present study area.…”
Section: Continental Fragmentsmentioning
confidence: 99%
“…Numerous previous studies have shown the potential for mantle lithosphere structures to control the evolution of shallow tectonics (Balázs et al, 2018;Heron et al, 2019;Jourdon et al, 2017;Pysklywec & Beaumont, 2004;Phillips et al, 2018;Salazar-Mora et al, 2018;Schiffer et al, 2018), highlighting a deep genesis for lithosphere-scale deformation (e.g., Holdsworth et al, 2001;Vauchez et al, 1997). Reactivation of features formed through previous collisional or rifting events (Wilson, 1966) is well established and thought to occur along well-defined, preexisting structures such as faults, shear zones, or lithological contacts (Holdsworth et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…West of Madagascar, a plate rearrangement led to the formation of the Davie Fracture Zone (DFZ) in the Tanzania Coastal Basin (TCB), overprinting the preexisting spreading center and fracture zones (Phethean et al, ). In Western Australia and the Jan Mayen Ridge near Greenland, changes in extension direction may have resulted in the formation of free‐moving microcontinents (e.g., Heine et al, ; Schiffer et al, ; Stagg et al, ; Whittaker et al, ). Finally, Davison et al () suggest the existence of conjugate zones of compressional deformation along the Romanche Fracture Zone.…”
Section: Introductionmentioning
confidence: 99%